Constructing an Achievement Test in Palestinian National Culture for Palestinian University Students Using the Rasch Unidimensional Model - Dabous, Mohammad Talab; Assaf, Mohammad Muhiuddin (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The study aimed to construct an achievement test in Palestinian national culture for university students using the Rasch unidimensional teacher model. To achieve the study’s objective, an achievement test in Palestinian national culture was constructed consisting of (50) dichotomous items of multiple-choice type. The test was administered to a sample of (606) male and female students from Palestinian universities in Palestine during the second semester of the academic year 2022/2023. For data analysis, the statistical programs Winsteps and SPSS were used. The alignment of the items of the achievement test in Palestinian national culture with the assumptions of the Rasch unidimensional teacher model was verified, where all items were found to align with the model’s assumptions. The test’s validity and reliability were also confirmed, with the results indicating a person separation reliability of (0.83) and an item separation reliability of (0.99). Based on the results, the researchers recommended the use of the test in Palestinian universities to assess students’ possession of Palestinian national culture.